PERAN DINAS PERINDUSTRIAN DAN TENAGA KERJA DALAM PEMBINAAN USAHA PANDAI BESI DI DESA TERATAK KECAMATAN RUMBIO JAYA TAHUN 2024 - Pasta, Haden El; ,, Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to determine the role of the industrial and labor services in developing blacksmith businesses and the inhibiting factors in developing blacksmith businesses in Teratak Village in 2024. This study uses the theory of the role of government by Gede Diva (2019) which states that there is an effective and optimal role of government in the development of SMEs realized as a facilitator, regulator and catalyst. This study uses qualitative methods. Data collection techniques include interviews and documentation. The results of this study indicate that the implementation of the government's role as a facilitator by the Kampar Regency Industry and Manpower Office has not yet reached its maximum level, so improvements are needed to increase its effectiveness. Meanwhile, the government's function as a regulator is already running and being implemented, but it is important to continue to pay attention to regulatory aspects to remain relevant to current developments. On the other hand, the government's role as a catalyst is considered quite effective, as evidenced by the various steps that have been taken to encourage the progress of SMEs, both in terms of human resource development and improving the quality of SMEs themselves. Keywords: The Role of Regional Government in Developing Blacksmith Businesses